2015
DOI: 10.4028/www.scientific.net/amm.816.54
|View full text |Cite
|
Sign up to set email alerts
|

Contact Problems between the Hub and the Shaft with a Four-Angular Shape of Cross-Section for Different Angular Positions

Abstract: The works [1, 2] present the values of the force and moment of friction needed to disassemble the axisymmetric connection with oval and three-angular shape of cross-section of the shaft. These works additionally show the variable values of the Mises stresses and contact pressures. This paper presents research which is a continuation of the research program on the evaluation of the influence of cross-section deviations, radial deviations, and their compilations on the value of the contact area in the connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Presented relationships have been applicable for FE analyses. Numerical and experimental tests have confirmed that the factor k = 0.3 was overstated [4,13] by author.…”
Section: Findley Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Presented relationships have been applicable for FE analyses. Numerical and experimental tests have confirmed that the factor k = 0.3 was overstated [4,13] by author.…”
Section: Findley Hypothesismentioning
confidence: 99%
“…At first we have to prepare the stress calculation process. This process is based on the expression of the j-th element membrane forces and bending moments (without shear forces) [13,14]…”
Section: Thin Shell Stress Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact with friction between sleeve and shaft was the first contact pair, Fig. 4, [8]. Assigned values are the same on both sides.…”
Section: Define Contactmentioning
confidence: 99%
“…It is used both for the preparation of semi-finished products and cutting of metal parts either for final use or as preparation for other technological operations [1,2]. Simple analytical calculations are usually used during preparation of serial manufacturing [3,4].…”
Section: Introductionmentioning
confidence: 99%